T-antigen-independent replication of polyomavirus DNA in murine embryonal carcinoma cells. - Dandolo, L (1984)
Expression of wild-type polyomavirus (Py) is restricted in murine embryonal carcinoma (EC) cells. The block appears to be located at the level of early transcription. Since no T antigen is produced, we investigated the fate of viral DNA upon infection of these cells; we showed that wild-type Py DNA replicates efficiently in all EC cells, probably via a T-antigen-independent mechanism. Furthermore, we studied, at permissive and restrictive temperatures, the replication of tsa (thermosensitive for T antigen) viral DNA of an in vitro-constructed deletion mutant lacking part of the early region coding sequences and of a double mutant carrying both the tsa mutation and the PyEC F9 mutation (allowing expression of early and late viral functions in EC cells). Our results imply that replication of wild-type A2 strain Py DNA can occur in EC cells in the absence of a functional T antigen. However, this protein clearly enhances viral DNA replication and is absolutely required in differentiated cells.